Thermodynamic assessment of power generation from waste heat in natural gas compressor station: A case study - Arif Karabuga; Murat Iskender; Behiye Yuksel; Elif Sultan Aydin; Zafer Utlu; Ferhat Eti (International Journal of Thermofluids)
This study presents a comprehensive thermodynamic and economic assessment of an Organic Rankine Cycle (ORC) system for waste heat recovery in natural gas compressor stations. The research systematically evaluates the impact of critical thermodynamic parameters, including turbine inlet temperature, pressure, working fluid flow rate, and exhaust gas temperature, on both energy and exergy efficiencies. The findings, system energy and exergy efficiencies increase by 22.52 % and 22.41 %, respectively. Additionally, an economic analysis was conducted to evaluate the feasibility of the system. The results indicate that higher turbine inlet temperatures contribute to lower LCOE, improving cost-effectiveness, while also enhancing sustainability through increased exergy efficiency. Additionally, a sensitivity analysis was performed using the Theil-Sen Robust Estimator, confirming that the system remains operationally stable across reasonable fluctuations in key parameters. These findings highlight ORC technology as an effective and sustainable solution for waste heat recovery, offering both economic and environmental benefits in industrial applications.